Pengaruh Model Project Based Learning Berbantu Media Pembelajaran Quizizz terhadap Hasil Belajar Siswa Mata Pelajaran Dasar Dasar Komputer di SMK 1 Painan - Oktavia, Wulandari; Hidayat, Hendra (Lembaga Yasin AlSys, 2025)
This study is motivated by the need for innovative learning models that can enhance students’ motivation, engagement, and learning outcomes in the subject of Computer Fundamentals. The purpose of this research is to examine the effect of implementing the Project-Based Learning (PJBL) model assisted by the interactive digital platform Quizizz on students’ learning outcomes at SMK Negeri 1 Painan. A quasi-experimental design was employed, involving two classes: an experimental group that received PJBL with Quizizz and a control group that was taught using the lecture method. The research subjects consisted of 50 students, with the study conducted from July 21 to August 6, 2025. Pre-tests and post-tests were administered to measure improvements in learning outcomes. The findings indicate that the post-test scores of the experimental group were significantly higher than those of the control group. These results affirm that integrating PJBL with Quizizz is effective in improving learning outcomes, motivation, engagement, and students’ critical thinking skills in computer networking.